Silages of sorghum, Tamani guinea grass, and Stylosanthes in an integrated system: production and quality - Prado, Laís Guerra; Costa, Kátia Aparecida de Pinho; da Silva, Luciana Maria; Costa, Adriano Carvalho; Severiano, Eduardo da Costa; Costa, João Victor Campos Pinho; Habermann, Eduardo; e Silva, João Antônio Gonçalves (Frontiers in Sustainable Food Systems, 2023)
Crop–livestock integration systems are efficient technologies for diversifying production and promoting agricultural sustainability. However, less is known about the triple intercropping of crops for silage production. The objective of this study was to evaluate the dry mass production, fermentation profile, and nutritive value of sorghum silage intercropped with Tamani guinea grass and Stylosanthes cv. Bela in integrated systems. We used an experimental design with randomized blocks with four replicates. The treatments consisted of silage of (1) sorghum in monocropped; (2) Tamani guinea grass in monocropped (Panicum maximum cv. BRS Tamani); (3) Stylosanthes cv. Bela in monocropped (Stylosanthes guianensis cv. BRS Bela); (4) sorghum intercropped with Tamani guinea grass; (5) sorghum intercropped with Stylosanthes cv. Bela; (6) Stylosanthes cv. Bela intercropped with Tamani guinea grass; and (7) sorghum intercropped with Tamani guinea grass and Stylosanthes cv. Bela, totaling 28 experimental silos. Our results demonstrated that intercropping sorghum with tropical forages can be utilized in integrated silage production systems. This practice led to an increase in silage mass production per unit area while also providing pasture forage after the crop harvest for silage production, ultimately enhancing land-use efficiency in a sustainable manner. Silage produced from sorghum intercropped with Tamani guinea grass and Stylosanthes cv. Bela exhibited improved fermentative characteristics, as well as higher ether extract and total digestible nutrient contents compared with silage from monocropped forages. Tropical forages contributed to an increase in the crude protein content of monocropped sorghum silage, which could potentially reduce costs associated with acquiring protein salts for ruminant feed supplementation. Consequently, we recommend the triple intercropping of sorghum, Tamani guinea grass, and Bela for silage production, as it offers advantages for the cultivation of annual and tropical forage crops.